Histopathological and immunohistochemical (cytokeratins AE1/AE3) study of the parametrium of patients with early stage cervical cancer - Candido, Eduardo B. [UNESP]; Silva-Filho, Agnaldo L. [UNESP]; Triginelli, Sergio A.; Pedrosa, Moises S.; Macarenco, Ricardo; Porto, Lucia; Traiman, Paulo [UNESP] (Elsevier B.V., 2008)
Objective: This study was under-taken in order to evaluate histopathological and immunohistochemical (cytokeratins AE1/AE3) characteristics of parametrial invasion in patients with early stage cervical cancer.Study design: Thirty patients with stage IB squamous cell carcinoma (SCC) of the cervix submitted to radical hysterectomy from November 2001 to September 2002 were prospectively studied. Histopathological studies were undertaken using tissue samples (n = 60) taken from the parametrium, whose surgical margins were inked and the entire parametrial tissue was fixed in 10% buffered formalin and embedded in paraffin for further analysis using hematoxylin-eosin (H&E) staining. Specific patterns of parametrial involvement (continuous invasion, parametrial lymphatic vascular space invasion (LVSI) and/or parametrial lymph nodes' (PMLN) metastasis) were recorded. Parametrial samples, in which the histological examination showed no tumor involvement, were immunohistochemically assessed through monoclonal antibodies for cytokeratins AE1/AE3. Clinicopathological characteristics of the patients were also recorded.Results: Patient's mean age was 49 +/- 10 years (27-73 years). Histopathological analysis (H&E) showed parametrium involvement in 12 patients (40%) of whom 11 (92%) presented parametrial LVSI, 9 (75%) continuous invasion and 4 (33%) PMLN metastasis. Micrometastasis was detected in 3/18 (17%) of the patients with histologically negative parametrium by H&E evaluation. Parametrial involvement detected by H&E was associated with tumor recurrence (p = 0.009) and survival (p = 0.025). This association was not correlated with the presence of parametrial micrometastasis (p = 1.00 and 1.00, respectively).Conclusions: The process of parametrial spreading in patients with SCC of the cervix may develop several histopathological patterns, which are associated with clinicopathological features and prognosis. Our findings highlight the importance to ink the parametria, which is the only way to define the pattern of tumor spreading. The clinical significance of micrometastasis, detected in patients with histologically negative parametrium by H&E, remains to be clear. (C) 2008 Published by Elsevier B.V.
Keywords: Cervix; Carcinoma; Parametrium; Cytokeratins